2019
DOI: 10.1080/10888438.2019.1643868
|View full text |Cite
|
Sign up to set email alerts
|

Considering the Role of Executive Function in Reading Comprehension: A Structural Equation Modeling Approach

Abstract: In the present study, we used latent variable structural equation modeling to investigate relations between oral language, decoding, and two components of executive function (cognitive flexibility and working memory) and reading comprehension in a sample of 271 native English-speaking 9.00-to 14.83-year-olds. Results of the mediation analyses indicated that both oral language and decoding fully mediated the relations between working memory and cognitive flexibility and reading comprehension. These findings sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
58
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 100 publications
11
58
0
3
Order By: Relevance
“…Thus, to test the assumption that executive functions have an effect on reading comprehension beyond fluent decoding and language skills and to minimize the measurement errors of executive functions, it is necessary to include multiple measures of executive functions and test their effect with latent variable constructs. Only a few recent studies have accomplished this goal (e.g., Spencer et al, 2019) and similarly rigorous research is still needed (see also Follmer, 2018;Keiffer et al, 2013).…”
Section: Limitations Of the Existing Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, to test the assumption that executive functions have an effect on reading comprehension beyond fluent decoding and language skills and to minimize the measurement errors of executive functions, it is necessary to include multiple measures of executive functions and test their effect with latent variable constructs. Only a few recent studies have accomplished this goal (e.g., Spencer et al, 2019) and similarly rigorous research is still needed (see also Follmer, 2018;Keiffer et al, 2013).…”
Section: Limitations Of the Existing Researchmentioning
confidence: 99%
“…Second, most studies that indicated an association between executive functions and reading comprehension were cross-sectional and did not explain the development of reading comprehension over time. For instance, only 4 out of 29 studies included in Follmer's analysis were longitudinal, and more recent studies had the same limitation (Cirino et al, 2019;Liu et al, 2018;Spencer et al, 2019). Yet, in order to understand the extent of which executive functions predict the development of reading comprehension, longitudinal studies are warranted (see also Keiffer et al, 2013).…”
Section: Limitations Of the Existing Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, although important language and cognitive predictors were included in the study, some potential predictors of reading comprehension were not examined. Those predictors include phonological knowledge ( Pan et al, 2016 ), morphological knowledge ( Zhang et al, 2012 ), inference making ( Tompkins et al, 2013 ), working memory ( Spencer et al, 2019 ), the theory of mind ( Kim, 2015 , 2016 ), and text structure knowledge ( Cain et al, 2004 ). For example, working memory, as a basic cognitive skill maintaining and processing information, is important to reading comprehension as there is frequent integration of information across sentences ( Oakhill, 2020 ).…”
Section: Limitation and Future Directionsmentioning
confidence: 99%